The diversity of tree species in Kalimpa’a Lake, Lore Lindu National Park - Agus Salim; Ramadhanil Pitopang; Samsurizal M Suleman (Biology Department, Mathematics and natural science, Tadulako University, 2019)
Diversity of tree species around Lake Kalimpa'a, Lore Lindu National Park has been implemented since July to September 2016. This research is descriptive and qualitative to know knowing the diversity of tree species and analyze the tree vegetation. The analysis of tree species was used quadratic method by using a single plot measuring 50 m x 50 m formed into 25 plots measuring 10 m x 10 m. The result of research, found 112 individual trees consist of 37 species. Some of them are classified as endemic species of Antidesma Celebicum Miq., Chionanthus celebicus Koord., Macaranga waturandangii Whitmore, and Lithocarpus menadoensis (Koord.) Soepadmo. Tree type Castanopsis acuminatissima (Blume) A.DC. has the highest importance index value of 41.78 and Garcinia sp. was the lowest important value index INP 2.41.